An Embellished Particle Swarm Optimization Technique in VANET for Finding Optimal Route (E-PSO) - Devi, S. Chithra; Maheswari, D. (SN computer science, 2022)
Traffic control system plays a major role in ITS (intelligent transport system). The activities in ITS are monitored by GPS which sends the warning messages to the traffic control room. Finding the optimal path was one of the important challenges in VANET. The main objective of this work is to find the shortest path by updating the frequently used path for better transportation. In this work, an efficient E-PSO algorithm is used to find the best path for vehicles to travel in a traffic. The algorithm calculates the function to find the vehicles’ position and updates its path. Updating the path increases its performance when compared with an existing work. The results show that the proposed work gains the performance up to 60–65% to find the optimal path by selecting the feasible route with good condition.